2004
DOI: 10.1002/app.13542
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the mechanical properties and interfacial interactions between talc, kaolin, and calcium carbonate filled polypropylene composites

Abstract: Three types of mineral fillers-talc, calcium carbonate (CaCO 3 ), and kaolin (10 -40 wt % filler loadings)-were compounded with polypropylene (PP) with a twin-screw extruder. The composites were injectionmolded, and the effects of the filler loading on the mechanical, flow, and thermal properties for the three different types of filled composites were investigated. The aim was to compare their properties and to deduce prospective filler combinations that would yield hybrid PP composites in following studies. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
257
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 273 publications
(285 citation statements)
references
References 20 publications
23
257
0
5
Order By: Relevance
“…These minerals can be value-added in terms of physical and chemical properties through various mineral processing techniques, in order to fulfill the filler specifications that are used in manufacturing industries such as polymer, paint, paper, ceramics, and construction [2]. On the basis of previous work [3][4][5][6][7][8], currently, the specifications for the minerals to be used as fillers in manufacturing processes are focused not only on the particle size but also on the particle shape, the particle size distribution, and the degree of crystallinity. The previous work [4] also observed that the degree of crystallinity of the mineral filler influenced the coefficient of thermal expansion (CTE) of mineral silica-filled epoxy composites.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These minerals can be value-added in terms of physical and chemical properties through various mineral processing techniques, in order to fulfill the filler specifications that are used in manufacturing industries such as polymer, paint, paper, ceramics, and construction [2]. On the basis of previous work [3][4][5][6][7][8], currently, the specifications for the minerals to be used as fillers in manufacturing processes are focused not only on the particle size but also on the particle shape, the particle size distribution, and the degree of crystallinity. The previous work [4] also observed that the degree of crystallinity of the mineral filler influenced the coefficient of thermal expansion (CTE) of mineral silica-filled epoxy composites.…”
Section: Introductionmentioning
confidence: 99%
“…Mineral particulate fillers are used in polymer composites to substitute for relatively costly bulk material and to share some mineral property with the host matrix, that is, to improve the properties of the matrix. Various types of mineral fillers such as talc, mica, wollastonite, and calcium carbonate were loaded into polymers [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are often modified by the introduction of fibrous fillers, sheet as well as powder. As stated in [1,8,14], the content of the filler in the polymer material can lead to increased stiffness, hardness, creep resistance, the ignition and combustion resistance, tensile strength and flexural strength and increasing resistance to the action of atmospheric factors.…”
Section: Introductionmentioning
confidence: 99%
“…Blending PP with inorganic fillers, such as silica (3)(4)(5) , calcium carbonate (6)(7)(8)(9)(10)(11)(12)(13)(14)(15) , talc (16)(17)(18)(19) , clay (20) and wollastonite (21,22) , is a useful way to improve physical and mechanical properties of polypropylene composites. The effects of inorganic fillers on the mechanical and physical properties of the PP composites strongly depend on the filler size, shape, aspect ration, interfacial adhesion, surface characteristics and degree of dispersion (5,15,23,24) .…”
Section: Introductionmentioning
confidence: 99%